Iris transluminance in type 2 diabetes - Voutilainen‐Kaunisto, Raija; Niskanen, Leo; Uusitupa, Matti; Teräsvirta, Markku (Acta ophthalmologica Scandinavica, 2002)
Purpose:  Cross‐sectional analysis of iris transluminance in type 2 diabetic patients compared with control subjects, all followed in a cohort study. Methods:  A cohort consisting of a well‐characterized group of 82 type 2 diabetic patients were followed for 10 years after diagnosis, as were 125 control subjects. The prevalence of iris transluminance was determined by transscleral transillumination and by grading of black‐and‐white positive prints at the 10‐year examination. The frequency of diabetic retinopathy was prospectively determined by grading of fundus photographs at baseline and after five and 10 years. Results:  Iris transluminance was found in 27% of diabetic patients and 8.0% of control subjects (P = 0.001). The diabetic patients with more severe and short‐term retinopathy more commonly had abnormal iris transluminance than those with no or only mild retinopathy (P < 0.05). Iris transluminance was not associated with intraocular pressure or glycemic control. Conclusions:  In type 2 diabetic patients, abnormal iris transluminance tended to associate with more severe and short‐term retinopathy. Therefore we assume that hypoxia is responsible for the defects in the pigment layer of the iris. Thus, abnormal iris transluminance may serve as a marker for rapidly progressive retinopathy.